The Impact of Exchange Rate Volatility on Foreign Direct Investment - BUSE, Oana Bianca (2012)
This study investigates the impact of exchange rate volatility on the level of foreign direct investment inflows in the Unites States of America, the United Kingdom, Canada and Japan, using annual data starting from 1975 to 2011. Exchange rate volatility has been measured using four different methods: a classic standard deviation, a moving mean difference value of the exchange rate fluctuations, a moving average standard deviation with a 3-year window and, finally, using a GARCH(1,1) model. The data was accounted for serial correlation, nonstationarity and cointegration and the relationship between inward FDI flows (expressed as a percentage of GDP for each country) and exchange rate volatility has been analyzed using OLS regressions and a panel data model, as well as an error correction model to investigate the existence of a short-term relationship between the two variables. While OLS estimates have shown that FDI inflows in three out of the four countries analyzed are influenced by exchange rate volatility, no evident link between the two variables has been found in the panel data analysis. In general, the mixed results obtained are proof that the existence of a relationship between FDI inflows and exchange rate volatility varies across countries and between different econometric models employed.